2020
DOI: 10.1039/d0ra05015f
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase inhibitors from Chinese bayberry (Morella rubraSieb. et Zucc.) fruit: molecular docking and interaction mechanism of flavonols with different B-ring hydroxylations

Abstract: Inhibition of α-glucosidase alleviates postprandial high glycemic levels in diabetic or prediabetic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 62 publications
3
47
0
Order By: Relevance
“…Kaempferol (K), quercetin (Q), and myricetin (M) are three major flavonol aglycones that differ in the number of hydroxyl groups on the B‐ring, with M (3′,4′,5′‐trihydroxy) having the highest number (Figure 1). M has been shown to be more beneficial for human health than either Q or K (Lu et al., 2006; Kumamoto et al., 2009; Liu et al., 2020). M has shown significant inhibitory effects on skin cancer (Jung et al., 2008), pancreatic cancer (Phillips et al., 2011), and α‐glucosidase activity (Liu et al., 2020), and is also an effective inhibitor of severe acute respiratory syndrome coronavirus helicase (Keum and Jeong, 2012; Yu et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaempferol (K), quercetin (Q), and myricetin (M) are three major flavonol aglycones that differ in the number of hydroxyl groups on the B‐ring, with M (3′,4′,5′‐trihydroxy) having the highest number (Figure 1). M has been shown to be more beneficial for human health than either Q or K (Lu et al., 2006; Kumamoto et al., 2009; Liu et al., 2020). M has shown significant inhibitory effects on skin cancer (Jung et al., 2008), pancreatic cancer (Phillips et al., 2011), and α‐glucosidase activity (Liu et al., 2020), and is also an effective inhibitor of severe acute respiratory syndrome coronavirus helicase (Keum and Jeong, 2012; Yu et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…M has been shown to be more beneficial for human health than either Q or K (Lu et al., 2006; Kumamoto et al., 2009; Liu et al., 2020). M has shown significant inhibitory effects on skin cancer (Jung et al., 2008), pancreatic cancer (Phillips et al., 2011), and α‐glucosidase activity (Liu et al., 2020), and is also an effective inhibitor of severe acute respiratory syndrome coronavirus helicase (Keum and Jeong, 2012; Yu et al., 2012). Recently, a myricetin derivative named montbretin A was identified by screening a library of 50 000 plant natural products as a specific inhibitor of human pancreatic α‐amylase and is therefore an important candidate therapeutic agent for diabetes and obesity treatments (Tarling et al., 2008; Williams et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that quercetin and kaempferol in S. lanuginosum and rosmarinic acid present on E. tinifolia are effective inhibitors of this enzyme [55,56]. Considering these compounds as the main polyphenols of extracts activity, the mechanism of α-glucosidase inhibition by wild fruit extracts could be due to the non-competitive or mixed-type interactions that polyphenols such as quercetin, kaempferol [57][58][59], and rosmarinic acid [60] maintain with the enzyme. Further studies must be done to determine the mechanism of action of S. lanuginosum and E. tinifolia extracts.…”
Section: Inhibition Of α-Glucosidasementioning
confidence: 99%
“…[1][2][3][4] Control of blood sugar levels is critical in diabetes therapy as it is associated with a marked reduction in the risk of developing complications such as neuropathy, retinopathy, or cardiovascular diseases. [5][6][7] α-Glucosidase plays an important role in carbohydrate digestion and glycoprotein biosynthesis. The inhibition of α-glucosidase involves two small intestinal membrane-bound enzymes: maltase-glucoamylase (MGAM) and sucrase-isomaltase (SI); these are implicated in the breakdown of dietary sugars and starches.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (MD) is a group of metabolic diseases characterized by high blood glucose levels (hyperglycemia), which play a pivotal role in the development of long‐term diabetic complications [1–4] . Control of blood sugar levels is critical in diabetes therapy as it is associated with a marked reduction in the risk of developing complications such as neuropathy, retinopathy, or cardiovascular diseases [5–7] …”
Section: Introductionmentioning
confidence: 99%